2021
DOI: 10.2147/cia.s339221
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Role of Systemic Inflammation Response Index (SIRI) in the Prognosis of Stroke Patients

Abstract: Purpose Stroke is a disease associated with high mortality. Many inflammatory indicators such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte to monocyte ratio (LMR) and red blood cell distribution width (RDW) have been documented to predict stroke prognosis, their predictive power is limited. A novel inflammatory indicator called systemic inflammatory response index (SIRI) has been advocated to have an essential role in the prognostic assessment of cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
95
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 44 publications
6
95
0
1
Order By: Relevance
“…SII and SIRI were novel indicators that assessed the balance between systemic inflammation and immune response in the body and had a better effect on reflecting the inflammatory state (17). Previous studies have confirmed that these indicators were more comprehensive and effective in evaluating inflammation levels and correlated with the prognosis of multiple chronic diseases and adverse CVD events (18)(19)(20)32). Among four indicators, we observed that MHR and SIRI expressed a significant association with metabolic diseases, both overall MetD and detailed MetS, dyslipidemia, and central obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SII and SIRI were novel indicators that assessed the balance between systemic inflammation and immune response in the body and had a better effect on reflecting the inflammatory state (17). Previous studies have confirmed that these indicators were more comprehensive and effective in evaluating inflammation levels and correlated with the prognosis of multiple chronic diseases and adverse CVD events (18)(19)(20)32). Among four indicators, we observed that MHR and SIRI expressed a significant association with metabolic diseases, both overall MetD and detailed MetS, dyslipidemia, and central obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The composite inflammatory indicators such as monocyteto-high-density lipoprotein ratio (MHR) (15), neutrophilto-lymphocyte ratio (NLR) (15), systematic immuneinflammation index (SII) (16), and systemic inflammation response index (SIRI) (17) are a novel type of parameters based on the traditional peripheral blood cell count, calculated by combining different biochemical parameters to balance inflammation and immunity status (17). Previous studies have confirmed that these indicators could reflect inflammation levels and were widely used in evaluating the risk of various chronic diseases and the prognosis of tumors (18)(19)(20)(21)(22). Therefore, our study enrolled and screened these four simple-to-calculate and easily accessible systemic inflammatory indicators to assess their effect in evaluating the risk of metabolic diseases and CVD, filling the knowledge gap on the association between inflammation and metabolic diseases at the individual level.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel indicator has emerged called the systemic inflammatory response index (SIRI). A composite index based on the absolute count of three different inflammatory cells, namely, neutrophils, monocytes, and lymphocytes, and it is highly associated with cancer, hyperuricemia, rheumatoid arthritis, and stroke (12)(13)(14)(15). However, the prognostic value of SIRI in elderly patients with HF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, SIRI is associated with many diseases. A higher SIRI is positively associated with the risk and poor prognosis of stroke [ 17 , 19 ]. SIRI has also been evaluated as a biomarker in the diagnosis and assessment of rheumatoid arthritis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%